Learning experience in swimming for children disorder Attention Deficit Hyperactivity Disorder (ADHD): Didatic and pedagogical aspects - Graffius Damascenov, Leonardo; Silveira de Queiroz, Sávio (Guará Journal, 2016)
The following study investigates male children behavior suffering from Attention Deficit Hyperactivity Disorder (ADHD), from the ages of 07 to 09 years old, in the performance of a sport activity. Based in a neuropsychological approach of the process, it supports the hypothesis of the positive effects that systematic and regular physical activity have on neurocognitive function and inhibitory control of children suffering from ADHD, showing the possibility of basic symptoms reduction in this group. Given the exploratory feature of the research, it was proposed a Swimming Learning Experimental Program, made out of a single step, consisting of 5 units, summing up a total of 21 classes. The results pointing to the attention deficit as being one of the main symptoms of ADHD, did not prove enough as to interfere with the children ́s activity performance. On the contrary, the hyperactivity and impulsiveness showed to be a positive conduct in challenging activities, because the child would not stop to think about the consequences, stimulating other apprehensive students in the swimming classes. An educational perspective it is concluded that the conduct of the children surveyed in this sample, resulting from the symptom picture installed by ADHD, were not detrimental to learning to swim.